Prevalence of risk factors for arterial hypertension among draft age youth - Basana V. Uvarovskaia (IP Morozov P.V., 2021)
Background. The currently observed diseases of the circulatory system getting younger, the increase in the incidence of arterial hypertension (AH) and the high mortality rate of men of working age in Russia are elements of one of the main medical and social problems. The identification of risk factors (RF) for the development of hypertension in young patients and the identification of the groups with the highest risk of cardiovascular events in their future adult life is aimed at preventing hypertension, early treatment initiation, increasing life expectancy and reducing mortality.